Postcolonial Reading of the Bible: (Evangelical) Friend or Foe? - Mamahit, Ferry Yefta (Jurnal Jaffray Vol 19, No 2, 2021)
Reading the Bible through a postcolonial lens has become today’s trend in biblical hermeneutics. It triggers pros and cons within the evangelical circle. Is it friend or foe? Rather than uncritically accepting or refusing it, the article chooses a middle way, being “open but cautious” toward it. The article assumes that every reading method has its strengths and weaknesses and, thus, it can offer valuable things. Applying the content analysis theory, the author finds that a postcolonial biblical reading is somehow relevant to a contextual and transformative biblical reading, regardless of its multiple problems. It enables the readers to be self-critical, context-sensitive, and practical in faith-life integration. The article concludes that postcolonial reading of the Bible can be both (evangelical) friend and foe.

Membaca Alkitab melalui lensa pascakolonial telah menjadi tren hermeneutika alkitabiah saat ini. Ini memicu pro dan kontra di kalangan Injili. Apakah itu teman atau musuh? Alih-alih menerima atau menolaknya tanpa kritik, artikel ini memilih jalan tengah, “terbuka tetapi berhati-hati” terhadapnya. Artikel ini berasumsi bahwa setiap metode membaca memiliki kelebihan dan kekurangannya masing-masing sehingga dapat menawarkan hal-hal yang berharga. Dengan menerapkan teori analisis isi, penulis menemukan bahwa pembacaan biblika pascakolonial entah bagaimana relevan dengan pembacaan alkitabiah yang kontekstual dan transformatif, terlepas dari berbagai masalahnya. Hal ini memungkinkan pembaca untuk menjadi kritis terhadap diri sendiri, peka dengan konteks, dan praktis dalam integrasi kehidupan iman. Artikel ini menyimpulkan bahwa pembacaan Alkitab pascakolonial dapat menjadi teman dan musuh (Injili).
Keywords: Postcolonialism; Evangelicalism; Biblical interpretation; Bible. -- Criticism, interpretation, etc.